Ketidakadilan Promosi dan Perubahan Attitude Karyawan Sebagai Pemicu Turunnya Loyalitas Serta Implikasinya Terhadap Strategi Manajemen SDM - Aristawidya, Ailen; Azzahra, Ardissa Nasya; Fadillah, Aura Rahma; Fitria, Rahma Najwa; Fadlillah, Zahra Faza (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the impact of promotion injustice on employee attitudes and loyalty using a PRISMA-based Systematic Literature Review (SLR). The findings show that unfair promotion practices reduce job satisfaction, weaken affective, normative, and continuance loyalty, and increase turnover risk. These results highlight the importance of transparent, performance-based promotion systems supported by consistent evaluations, clear communication, and career development initiatives. The study also strengthens theoretical understanding by integrating Social Exchange Theory and Organizational Justice Theory within the context of strategic human resource management.